Sodium secondary battery and electric device

CN122931005APending Publication Date: 2026-10-16CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611394330.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-11-09
Filing Date
2024-03-05
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]在资源和成本方面,钠二次电池比锂二次电池具有更大的优势,但是钠二次电池产气严重,限制了其进一步应用

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931005A_ABST
    Figure CN122931005A_ABST
Patent Text Reader

Abstract

The application provides a sodium secondary battery and an electric device. The sodium secondary battery comprises a negative electrode sheet and an electrolyte. The negative electrode sheet comprises a negative electrode active material. The ratio of the actual discharge specific capacity of the negative electrode active material measured by a three-stage gradual discharge method of discharging at a 0.05C rate first and then discharging at a 40 muA and 10 muA current in a 1.0V-0.5V voltage interval to the theoretical discharge specific capacity of the negative electrode active material is a. The electrolyte comprises a first component. The first component is a fluorinated carbonate compound. The mass fraction of the fluorinated carbonate compound in the total mass of the electrolyte is b. And a and b satisfy: 1<=a / b<=270. The sodium secondary battery can reduce the volume expansion rate of the battery after high-temperature storage, improve the low-temperature charging performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the invention with application number 202480071588.1, application date March 5, 2024, applicant CATL, and invention title "Sodium Secondary Battery and Power Consumption Device". Technical Field

[0002] This application relates to the field of secondary battery technology, and in particular to a sodium secondary battery and an electrical device thereof. Background Technology

[0003] In recent years, rechargeable batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric cars, military equipment, aerospace, and many other fields. With the increasing application of rechargeable batteries, higher requirements have been placed on their cycle performance and service life.

[0004] In terms of resources and cost, sodium-ion batteries have a greater advantage than lithium-ion batteries, but sodium-ion batteries produce a lot of gas, which limits their further application. Summary of the Invention

[0005] This application is made in view of the above-mentioned problems, and its purpose is to provide a sodium secondary battery for reducing gas production in sodium secondary batteries and improving the cycle stability of the battery.

[0006] The first aspect of this application provides a sodium secondary battery, which includes a negative electrode and an electrolyte. The negative electrode includes a negative active material. The ratio of the actual discharge specific capacity of the negative active material measured by a three-stage step-by-step discharge method (discharging at a rate of 0.05C in a voltage range of 1.0V-0.5V, followed by discharging at currents of 40μA and 10μA) to the theoretical discharge specific capacity of the negative active material is a. The electrolyte includes a first component, which is a fluorocarbonate compound. Based on the total mass of the electrolyte, the mass percentage of the fluorocarbonate compound is b, and a and b satisfy: 1≤a / b≤270, which can be optionally 1≤a / b≤100.

[0007] The solid electrolyte interphase (SEI) film on the negative electrode surface is prone to dissolution or decomposition in the 1.0V-0.5V voltage range, exposing the negative electrode to the electrolyte and causing reactions. Solvent molecules decompose on the electrode surface, easily generating gas, resulting in a high battery expansion rate and producing soluble byproducts. These byproducts can trigger irreversible side reactions, reducing the overall cycle stability and kinetic performance of the system. The higher the actual discharge specific capacity of the negative electrode active material in the 1.0V-0.5V voltage range, the more SEI film will form due to hard carbon defects and surface functional groups during sodium absorption. This leads to greater dissolution or decomposition of the SEI film during discharge in the 1.0V-0.5V voltage range. Fluorocarbonate compounds, through the electron-withdrawing effect of fluorine atoms, possess a lower LUMO energy, allowing them to be reduced and form an SEI film on the negative electrode surface in the relatively higher 1.0V-0.5V voltage range. This compensates for the increased gas production and decreased cycle stability caused by SEI film decomposition.

[0008] When the a / b ratio is within a suitable range, the negative electrode and electrolyte can work synergistically to improve the stability of the SEI film, thereby reducing gas production in the secondary battery and enhancing its kinetic performance and cycle stability. When a and b in the secondary battery satisfy 1 ≤ a / b ≤ 100, the battery's volume expansion rate, low-temperature charging performance, and room-temperature cycle capacity retention are further improved.

[0009] In any embodiment, the actual discharge specific capacity of the negative electrode active material, measured by a three-stage step-by-step discharge method of first discharging at a rate of 0.05C in the voltage range of 1.0V-0.5V and then discharging at currents of 40μA and 10μA, is 9mAh / g-140mAh / g, and can be selected as 18mAh / g-70mAh / g.

[0010] When the actual discharge specific capacity of the negative electrode active material is within a suitable range in the 1.0V-0.5V voltage range, the battery exhibits low gas production, excellent kinetic performance, and cycle stability. Negative electrode sheets with an actual discharge specific capacity of 18mAh / g-70mAh / g in the 1.0V-0.5V voltage range can balance low gas production, high cycle stability, and high energy density.

[0011] In any embodiment, based on the total mass of the electrolyte, the mass percentage b of the fluorocarbonate compound is 0.05% to 10%, and can be selected as 0.2% to 10%.

[0012] Based on the total mass of the electrolyte, when the mass percentage (b) of fluoroethylene carbonate in the electrolyte is 0.05%-10%, the battery exhibits low volume expansion rate after high-temperature storage, excellent low-temperature charging performance, and good capacity retention during room-temperature cycling. When the mass percentage (b) of fluoroethylene carbonate in the electrolyte is 0.2%-10%, the volume expansion rate after high-temperature storage can be further reduced, and the low-temperature charging performance and capacity retention during room-temperature cycling can be improved.

[0013] In any embodiment, the fluorocarbonate compound includes the compound shown in Formula I. Formula I Among them, R1, R2, R3, and R4 each independently include hydrogen atoms, halogen atoms, and carbon atoms. 1-6 hydrocarbon group, C 1-3 Haloalkyl, C 1-3 Alkoxy, C 1-3 At least one of haloalkoxy, ester, cyano, sulfonic acid, and isocyanate groups; and at least one of R1, R2, R3, and R4 is a fluorine atom.

[0014] Cyclic fluorocarbonates in which at least one of R1, R2, R3, and R4 is a fluorine atom are easy to open, forming an SEI film on the negative electrode surface, reducing battery gas production, and improving battery dynamic performance and cycle stability.

[0015] In any embodiment, the fluorocarbonate compound includes at least one of the following compounds: Formula II-1 Formula II-2 Formula II-3 Formula II-4 Formula II-5 Formula II-6 Formula II-7 Formula II-8 Formula II-9 Formula II-10.

[0016] In any embodiment, the negative electrode sheet includes a negative electrode film layer containing calcium.

[0017] Introducing calcium into the negative electrode film can induce sodium ion deposition, which helps to suppress sodium dendrite formation and reduce the oxidation and gas production of unstable components generated by sodium dendrites on the negative electrode. This reduces the amount of gas produced by the negative electrode during discharge and lowers the volume expansion rate of the battery after high-temperature storage.

[0018] In any embodiment, based on the total mass of the negative electrode film, the mass percentage of calcium in the negative electrode film is d. The ratio of the actual discharge specific capacity measured by the three-stage stepwise discharge method (discharging at a rate of 0.05C first, then at currents of 40μA and 10μA) to the theoretical discharge specific capacity of the negative electrode active material is c, and d and c satisfy: 2.5 × 10⁻⁶. -6 ≤d / c≤4.5×10 -3 5.5×10 can be selected. -5 ≤d / c≤3.1×10 -3 .

[0019] Unlike lithium-ion batteries, sodium-ion batteries often use hard carbon as their negative electrode active material. The capacity utilization of hard carbon mainly consists of two stages. The first stage is between 1.5V and 0.1V (vs Na / Na). + The capacity of ) comes from Na + The adsorption process at defects on the hard carbon surface, the second stage is at 0.1V (vsNa / Na) + The following capacity contribution comes from Na + The filling process within the micropores of hard carbon. To improve the negative electrode capacity, existing technologies often increase the porosity of hard carbon. However, Na... + The potential during the hard carbon micropore filling process is close to the potential for sodium deposition (0V), which easily leads to sodium deposition during charging. The deposited sodium dendrites are highly reactive and react rapidly with the electrolyte to produce a large amount of gas and unstable byproducts. These unstable substances are prone to oxidative decomposition during discharge as the negative electrode potential increases and the film-forming driving force becomes insufficient. In addition, unstable organic byproducts easily dissolve in the electrolyte, causing the SEI film to be in a constant cycle of dissolution and repair, exacerbating battery gas production and deteriorating cycle stability.

[0020] Calcium in the negative electrode film can induce sodium ion deposition on the negative electrode, helping to suppress sodium dendrite formation and thus reducing unstable components caused by sodium dendrites. When the d / c value is within a suitable range, the interaction between calcium in the negative electrode film and the active material in the negative electrode sheet allows the secondary battery to maintain high capacity and high energy density while exhibiting low gas production rate, high kinetic performance, and cycle stability.

[0021] In any embodiment, based on the total mass of the negative electrode film, the mass percentage d of calcium in the negative electrode film is 2ppm to 3000ppm, and can be selected as 40ppm to 2300ppm.

[0022] When the mass percentage (d) of calcium in the negative electrode film is within a suitable range, it can reduce the negative impact of excessive calcium content on the capacity and impedance of the secondary battery, while also fully leveraging the role of calcium in suppressing dendrite formation and reducing gas production. This reduces battery gas production while improving the battery's low-temperature charging performance and room-temperature cycle capacity retention. When the mass percentage (d) of calcium in the negative electrode film is between 40 ppm and 2300 ppm, the battery gas production rate is further reduced, and the cycle stability is further improved.

[0023] In any embodiment, the actual discharge specific capacity of the negative electrode active material, measured by a three-stage step-by-step discharge method of first discharging at a rate of 0.05C in the voltage range of 0.1V-0.005V and then discharging at currents of 40μA and 10μA, is 100mAh / g-300mAh / g, and can be selected as 200mAh / g-250mAh / g.

[0024] When the actual discharge specific capacity of the negative electrode active material is within a suitable range in the 0.1V-0.005V voltage range, it can reduce the amount of gas generated after the battery is stored at high temperatures, and improve the battery's kinetic performance and cycle stability. When the actual discharge specific capacity of the negative electrode active material in the 0.1V-0.005V voltage range is 200mAh / g-250mAh / g, it can further balance the battery's high energy density and low gas generation.

[0025] In any embodiment, the negative electrode active material comprises hard carbon.

[0026] In any embodiment, the sodium secondary battery further includes a positive electrode sheet, which comprises a positive electrode active material.

[0027] In any embodiment, the positive electrode active material further contains copper, and the mass percentage of copper is 0.01% to 23% based on the total mass of the positive electrode active material, and can be selected as 6.5% to 18%.

[0028] Positive electrode active materials containing copper have a more stable structure, which can further improve the cycle stability of the battery.

[0029] When the mass percentage of copper is within a suitable range, the battery's cycle stability is improved, and copper will not be converted into Cu under high voltage. 3+ This causes the electrolyte to decompose more rapidly under its high oxidizing properties, worsening the gas production phenomenon in the battery. A copper content ranging from 6.5% to 18% by mass can further balance the low gas production and high cycle stability of the secondary battery.

[0030] In any embodiment, the positive electrode active material comprises a sodium transition metal oxide, wherein the sodium transition metal oxide comprises Na m Cu n Xo Fe p Mn q O 2-s, Where X includes one or more of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn, Fe, and Ba, 0 <m≤1,0≤n≤0.5,0≤o<0.5,0≤p≤0.5,0<q≤0 .68,n+o+p+q=1,0≤s<0.2; In some embodiments, the sodium transition metal oxide includes Na[Cu] 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2, Na 7 / 9 [Cu 2 / 9 Fe 1 / 9 Mn 2 / 3 O2, Na 9 / 10 [Cu 2 / 5 Fe 1 / 10 Mn 1 / 2 At least one of O2.

[0031] Sodium transition metal oxide cathode active materials have high voltage. While the anionic oxygen contributes to capacity, it also generates a large amount of protonated hydrogen, accelerating the oxidation and gas production of unstable components in the negative electrode, resulting in severe gas production on the negative electrode side. Through the combined action of the negative electrode sheet provided in this application and the fluorocarbonate compounds in the electrolyte, battery gas production can be effectively reduced while improving battery capacity and energy density.

[0032] In any embodiment, the electrolyte further includes a second component, which is one or more of the following: vinylene carbonate, ethylene ethylene carbonate, 1,3-propane sulfonyl lactone, 1,3-propene sulfonate lactone, vinyl sulfate, maleic anhydride, succinic anhydride, sodium difluorooxalate borate, triallyl phosphate, sodium bis(oxalate) borate, sodium tetrafluorooxalate phosphate, sodium difluorobis(oxalate) phosphate, sodium difluorophosphate, and sodium fluorosulfonate.

[0033] The SEI film formed at the negative electrode interface in sodium-ion batteries mainly consists of sodium alkyl carbonate and sodium carbonate. However, sodium alkyl carbonate has a higher solubility in the electrolyte solvent than lithium alkyl carbonate, making the SEI film of sodium-ion batteries highly unstable. This leads to continuous side reactions between the electrolyte and the negative electrode, resulting in poor cycle performance. A second component containing unsaturated functional groups can preferentially reduce to form a film at the negative electrode compared to the solvent. It works in conjunction with fluorocarbonate compounds to inhibit the formation of easily soluble substances such as sodium alkyl carbonate, and together with the negative electrode sheet, reduces gas production and improves battery cycle stability.

[0034] In any embodiment, based on the total mass of the electrolyte, the mass percentage of the second component is 0.01% to 10%, and optionally 0.1% to 5%.

[0035] When the mass percentage of the second component is within the aforementioned range, it can improve the gas generation phenomenon in the battery while controlling the thickness of the SEI film, thereby simultaneously achieving low impedance and low gas generation in the battery.

[0036] A second aspect of this application also provides an electrical device, including the sodium secondary battery of the first aspect. Attached Figure Description

[0037] Figure 1 This is a schematic diagram of the charge-discharge curve test of the negative electrode sheet according to one embodiment of this application; Figure 2 This is a schematic diagram of a secondary battery according to one embodiment of this application; Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of this application is shown; Figure 4 This is a schematic diagram of a battery module according to one embodiment of this application; Figure 5 This is a schematic diagram of a battery pack according to one embodiment of this application; Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of this application is shown; Figure 7 This is a schematic diagram of an electrical device that uses a secondary battery as a power source according to one embodiment of this application.

[0038] Explanation of reference numerals in the attached figures: 1 Battery pack; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Sodium secondary battery; 51 Casing; 52 Electrode assembly; 53 Cover plate. Detailed Implementation

[0039] The embodiments of the sodium secondary battery and power-consuming device of this application are hereby disclosed in detail with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0040] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0041] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0042] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0043] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0044] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0045] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0046] In existing technologies, it is generally believed that gas production in sodium-ion batteries mainly originates from the oxidation of the electrolyte by the positive electrode active material under high voltage. Therefore, existing technologies often employ methods such as coating the positive electrode active material and forming a film on the positive electrode surface to reduce gas production in secondary batteries. During the research process, the applicant discovered that another important factor contributing to gas production in sodium-ion batteries lies in the negative electrode. The solid electrolyte interface (SEI film) on the surface of the negative electrode plays a crucial role in reducing gas production. However, during battery charge-discharge cycles, the SEI film undergoes a cyclical process of dissolution and repair, which easily leads to gas production and deterioration of battery cycle stability.

[0047] Sodium secondary battery Based on this, this application proposes a sodium secondary battery, comprising a negative electrode and an electrolyte. The negative electrode comprises a negative electrode active material. The ratio of the actual discharge specific capacity measured by a three-stage step-by-step discharge method (discharging at a rate of 0.05C first, then at currents of 40μA and 10μA within a voltage range of 1.0V-0.5V) to the theoretical discharge specific capacity of the negative electrode active material is 'a'. The electrolyte comprises a first component, which includes a fluorocarbonate compound. Based on the total mass of the electrolyte, the mass percentage of the fluorocarbonate compound is 'b', and 'a' and 'b' satisfy: 1 ​​≤ a / b ≤ 270. In some embodiments, 'a' and 'b' satisfy: 1 ​​≤ a / b ≤ 100.

[0048] A sodium secondary battery is a type of secondary battery that mainly relies on the movement of sodium ions between the positive and negative electrodes to function.

[0049] The actual discharge specific capacity of the negative electrode active material can be measured using the charge-discharge curve of a coin cell. The test method is a three-stage step-discharge method: first, discharge at a rate of 0.05C, then discharge at currents of 40μA and 10μA to reduce incomplete capacity utilization caused by polarization under high-rate discharge. As an example of the three-stage step-discharge method, the negative electrode sheet from a sodium secondary battery is punched into a small circular piece with a diameter of 14mm, which serves as the positive electrode in the coin cell. A metallic sodium sheet is used as the negative electrode, and a 1.3mol / L sodium hexafluorophosphate solution is used as the electrolyte. The electrolyte contains ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a mass ratio of 1:2:2. The coin cell is assembled, and a constant current charge-discharge test is performed in the voltage range of 0.005-2V. The charge-discharge curve is shown in the figure below. Figure 1As shown. The discharge process involves constant current discharge at a rate of 0.05C to 0.005V, followed by resting until the voltage recovers to a stable value E, then constant current discharge at a rate of 40μA to 0.005V, and finally resting until the voltage recovers to a stable value F, followed by constant current discharge at a rate of 10μA to 0.005V. The charging process involves constant current charging at a rate of 0.05C to 2V. The total capacity (mAh) of the discharge process within the voltage range of 1.0V-0.5V during the second charge-discharge cycle is divided by the mass (g) of the negative electrode active material in the negative electrode sheet, and recorded as the actual discharge specific capacity (mAh / g) of the negative electrode active material from 1.0V to 0.5V. For example... Figure 1 As shown, the difference between the specific capacity B corresponding to 0.5V and the specific capacity A corresponding to 1V in the discharge curve is the actual discharge specific capacity (mAh / g) of the negative electrode active material in the voltage range of 1.0V-0.5V. The charge-discharge curve can be measured by any electrochemical testing system in this field. As an example, it was obtained by using the Blue Electric Testing System CT3002A 1U model instrument.

[0050] In some embodiments, the negative electrode active material includes hard carbon, which has a theoretical discharge specific capacity of 300 mAh / g.

[0051] Fluorinated carbonate compounds are compounds containing a carbonate group (-OC(O)O-) in which at least one hydrogen atom is replaced by a fluorine atom. They can be linear or cyclic compounds.

[0052] The organic components of the solid electrolyte interphase (SEI) film on the negative electrode surface are prone to dissolution or decomposition in the 1.0V-0.5V voltage range. This exposes the negative electrode to the electrolyte, causing reactions. Solvent molecules continuously decompose on the electrode surface, generating gas and resulting in a high battery expansion rate. Furthermore, soluble byproducts are produced, which can trigger irreversible side reactions, reducing the overall cycle stability and kinetic performance of the system. The higher the actual discharge specific capacity of the negative electrode active material in the 1.0V-0.5V voltage range, the more SEI film is formed by hard carbon defects and surface functional groups during sodium absorption. This leads to greater dissolution or decomposition of the SEI film during discharge in the 1.0V-0.5V voltage range. Fluorocarbonate compounds, through the electron-withdrawing effect of fluorine atoms, can enhance the electron-accepting ability of the central atom. In the relatively high voltage range of 1.0V-0.5V, they can reduce and form an SEI film on the negative electrode surface to compensate for the increased gas production and decreased cycle stability caused by SEI film decomposition.

[0053] In some implementations, the value of a / b can be selected as 1, 1.3, 2.7, 3, 5, 6.1, 10, 13.3, 15, 20, 23.3, 30, 40, 46.7, 50, 60, 66.7, 70, 80, 90, 100, 150, 200, 250, 266.7, 270, or any range between the two.

[0054] Within the aforementioned range, the negative electrode and electrolyte can synergistically improve the stability of the SEI film, thereby reducing gas production in the secondary battery and enhancing its kinetic performance and cycle stability. When a and b in the secondary battery satisfy 1 ≤ a / b ≤ 100, the battery's volume expansion rate, low-temperature charging performance, and room-temperature cycle capacity retention are further improved.

[0055] In some embodiments, the actual discharge specific capacity of the negative electrode active material, measured by a three-stage step-discharge method (discharging at a rate of 0.05C within a voltage range of 1.0V-0.5V, followed by discharge at currents of 40μA and 10μA), is 9mAh / g-140mAh / g. In other embodiments, the actual discharge specific capacity of the negative electrode active material, measured by a three-stage step-discharge method (discharging at a rate of 0.05C within a voltage range of 1.0V-0.5V, followed by discharge at currents of 40μA and 10μA), is 18mAh / g-70mAh / g.

[0056] In some embodiments, the actual discharge specific capacity measured by the three-stage step-by-step discharge method, in which the negative electrode active material is first discharged at a rate of 0.05C in the voltage range of 1.0V-0.5V, and then discharged at currents of 40μA and 10μA, can be selected as 9mAh / g, 15 mAh / g, 18mAh / g, 20mAh / g, 30mAh / g, 40mAh / g, 50mAh / g, 60mAh / g, 70mAh / g, 80mAh / g, 90mAh / g, 100mAh / g, 110mAh / g, 120mAh / g, 130mAh / g, 140mAh / g, or any value between them.

[0057] The actual discharge specific capacity of the negative electrode active material, measured by a three-stage stepwise discharge method (discharging at a rate of 0.05C first, then at currents of 40μA and 10μA within a voltage range of 1.0V-0.5V), can be controlled by altering the preparation process of the negative electrode active material. Taking hard carbon as an example, by changing the pyrolysis temperature, the defect degree and porosity of the negative electrode active material surface can be adjusted to achieve capacity control in different voltage ranges. Increasing the pyrolysis temperature of hard carbon helps reduce surface defects, decreases sodium adsorption, and lowers its actual discharge specific capacity in the 1.0V-0.5V voltage range.

[0058] Batteries within the aforementioned range exhibit low gas production, excellent kinetic performance, and cycle stability. Anode plates with actual discharge specific capacities of 18 mAh / g to 70 mAh / g in the 1.0V-0.5V voltage range can balance low gas production, high cycle stability, and high energy density.

[0059] In some embodiments, the mass percentage b of the fluorocarbonate compound is 0.05% to 10% based on the total mass of the electrolyte. In some embodiments, the mass percentage b of the fluorocarbonate compound is 0.2% to 10% based on the total mass of the electrolyte.

[0060] In some embodiments, the mass percentage b of the fluorocarbonate compound, based on the total mass of the electrolyte, can be selected as 0.05%, 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any value between these values.

[0061] Based on the total mass of the electrolyte, when the mass percentage (b) of fluoroethylene carbonate in the electrolyte is 0.05%-10%, the battery exhibits low volume expansion rate after high-temperature storage, excellent low-temperature charging performance, and good capacity retention during room-temperature cycling. Based on the total mass of the electrolyte, when the mass percentage (b) of fluoroethylene carbonate in the electrolyte is 0.2%-10%, the battery volume expansion rate after high-temperature storage can be further reduced, and low-temperature charging performance and capacity retention during room-temperature cycling can be improved.

[0062] In some embodiments, the fluorocarbonate compound includes compounds represented by Formula I. Formula I Among them, R1, R2, R3, and R4 each independently include hydrogen atoms, halogen atoms, and carbon atoms. 1-6 hydrocarbon group, C 1-3 Haloalkyl, C 1-3 Alkoxy, C 1-3 At least one of haloalkoxy, ester, cyano, sulfonic acid, and isocyanate groups; and at least one of R1, R2, R3, and R4 is a fluorine atom.

[0063] In this article, the term "halogen atom" refers to elements in Group VIIA of the periodic table, including but not limited to: F, Cl, Br, and I.

[0064] In this article, the term "C" 1-6 "Hydrocarbon group" refers to a group containing carbon and hydrogen atoms, comprising 1 to 6 carbon atoms. In some embodiments, C 1-6The hydrocarbon group does not include unsaturated bonds and is an alkyl group. Examples include, but are not limited to, methyl, ethyl, propyl, isopropyl, 2-methyl-1-propyl, 2-methyl-2-propyl, 2-methyl-1-butyl, 3-methyl-1-butyl, 2-methyl-3-butyl, 2,2-dimethyl-1-propyl, 2-methyl-1-pentyl, 3-methyl-1-pentyl, 4-methyl-1-pentyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 2,2-dimethyl-1-butyl, 3,3-dimethyl-1-butyl, 2-ethyl-1-butyl, butyl, isobutyl, tert-butyl, pentyl, isopentyl, neopentyl, and hexyl. In some embodiments, C... 1-6 The hydrocarbon group includes unsaturated bonds, such as cycloalkyl, alkenyl, alkynyl, and aryl, and by way of example, includes but is not limited to cyclopropyl, cyclobutyl, vinyl, 1-propenyl or 2-propenyl, phenyl, and naphthyl.

[0065] In this article, the term "C" 1-3 "Halogenated alkyl" refers to a C-type alkyl group in which at least one hydrogen atom is replaced by a halogen atom. 1-3 Alkyl groups, for example including but not limited to: -CF3, -CF2CH2, -CF2CH2CH3.

[0066] In this article, the term "C" 1-3 "Alkoxy" refers to a carbon atom connected to the main carbon chain via an oxygen atom. 1-3 Alkyl groups, as examples, include, but are not limited to, methoxy (CH3O-), ethoxy (C2H5O-), and propoxy (C3H7O-).

[0067] In this article, the term "C" 1-3 "Haloalkoxy" refers to a carbon atom in which at least one hydrogen atom is replaced by a halogen atom. 1-3 Alkyl group.

[0068] In this article, the term "ester group" refers to the -COO- group.

[0069] In this article, the term "cyano" refers to the -CN group.

[0070] In this paper, the term "sulfonic acid group" refers to the -SO3H group.

[0071] In this article, the term "isocyanate group" refers to the -NCO group.

[0072] Cyclic fluorocarbonates in which at least one of R1, R2, R3, and R4 is a fluorine atom are easy to open, forming an SEI film on the negative electrode surface, reducing battery gas production, and improving battery dynamic performance and cycle stability.

[0073] In some embodiments, the fluorocarbonate compound includes at least one of the following compounds: Formula II-1 Formula II-2 Formula II-3 Formula II-4 Formula II-5 Formula II-6 Formula II-7 Formula II-8 Formula II-9 Formula II-10.

[0074] In some embodiments, the negative electrode sheet includes a negative electrode film layer containing calcium.

[0075] It is understood that calcium can be introduced into the negative electrode film in any form. In some embodiments, calcium is introduced into the negative electrode film in the form of calcium oxide or calcium salt. In some embodiments, calcium is introduced into the negative electrode film in the form of CaO.

[0076] Introducing calcium into the negative electrode film can induce sodium ion deposition, which helps to suppress sodium dendrite formation and reduce the oxidation and gas production of unstable components generated by sodium dendrites on the negative electrode. This reduces the amount of gas produced by the negative electrode during discharge and lowers the volume expansion rate of the battery after high-temperature storage.

[0077] In some embodiments, based on the total mass of the negative electrode film, the mass percentage of calcium in the negative electrode film is d. The ratio of the actual discharge specific capacity measured by a three-stage stepwise discharge method (discharging at a rate of 0.05C first, then at currents of 40μA and 10μA in the voltage range of 0.1V-0.005V) to the theoretical discharge specific capacity of the negative electrode active material is c, and d and c satisfy: 2.5 × 10⁻⁶. -6 ≤d / c≤4.5×10 -3 In some implementations, d and c satisfy: 5.5 × 10 -5 ≤d / c≤3.1×10 -3 .

[0078] In some implementations, the value of d / c can be selected as 2.5 × 10⁻⁶. -6 3×10 -6 4.5×10 -6 1.0×10 -5 1.1×10 -5 1.3×10 -5 1.4×10 -5 5.5×10 -5 1.0×10 -4 1.2×10 -4 1.4×10-4 1.5×10 -4 3.0×10 -4 4.0×10 -4 5.0×10 -4 6.0×10 -4 7.0×10 -4 8.0×10 -4 9.0×10 -4 1.0×10 -3 2.0×10 -3 3.0×10 -3 4.0×10 -3 4.5×10 -3 Or any value in between.

[0079] The actual discharge specific capacity of the negative electrode active material can be measured using the charge-discharge curve of a coin cell. The test method is a three-stage step-discharge method: first, discharge at a rate of 0.05C, then discharge at currents of 40μA and 10μA to reduce incomplete capacity utilization caused by polarization under high-rate discharge. As an example, the negative electrode sheet from a sodium secondary battery is cut into small circular pieces with a diameter of 14mm to serve as the positive electrode in the coin cell. A metallic sodium sheet is used as the negative electrode, and a 1.3mol / L sodium hexafluorophosphate solution is used as the electrolyte. The electrolyte contains ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a mass ratio of 1:2:2. A coin cell is assembled, and a constant current charge-discharge test is performed in the voltage range of 0.005V-2V. The charge-discharge curve diagram is shown below. Figure 1 As shown. The discharge process involves constant current discharge at a rate of 0.05C to 0.005V, followed by resting until the voltage recovers to a stable value E, then constant current discharge at a rate of 40μA to 0.005V, and finally resting until the voltage recovers to a stable value F, followed by constant current discharge at a rate of 10μA to 0.005V. The charging process involves constant current charging at a rate of 0.05C to 2V. The total capacity within the voltage range of 0.1V-0.005V during the second charge-discharge cycle is divided by the mass of the negative electrode active material in the negative electrode sheet, and this is recorded as the actual discharge specific capacity (mAh / g) of the negative electrode active material from 0.1V to 0.005V. For example... Figure 1 As shown, the difference between the specific capacity D corresponding to constant current discharge at a rate of 10μA to 0.005V and the specific capacity C corresponding to 0.1V in the discharge curve is the actual discharge specific capacity (mAh / g) of the negative electrode in the voltage range of 0.1V-0.005V.

[0080] In some embodiments, the negative electrode active material includes hard carbon, which has a theoretical discharge specific capacity of 300 mAh / g.

[0081] Unlike lithium-ion batteries, sodium-ion batteries often use hard carbon as their negative electrode active material. The capacity utilization of hard carbon mainly consists of two stages. The first stage is between 1.5V and 0.1V (vs Na / Na). + The capacity of ) comes from Na + The adsorption process at defects on the hard carbon surface, the second stage is at 0.1V (vsNa / Na) + The following capacity contribution comes from Na + The filling process within the micropores of hard carbon. To improve the negative electrode capacity, existing technologies often increase the porosity of hard carbon. However, Na... + The potential during the hard carbon micropore filling process is close to the potential for sodium deposition (0V), which easily leads to sodium deposition during charging. The deposited sodium dendrites are highly reactive and react rapidly with the electrolyte to produce a large amount of gas and unstable byproducts. These unstable substances are prone to oxidative decomposition during discharge as the negative electrode potential increases and the film-forming driving force becomes insufficient. In addition, unstable organic byproducts easily dissolve in the electrolyte, causing the SEI film to be in a constant cycle of dissolution and repair, exacerbating battery gas production and deteriorating cycle stability.

[0082] Calcium in the negative electrode film can induce sodium ion deposition at the negative electrode, helping to suppress sodium dendrite formation and thus reducing unstable components caused by sodium dendrites. When the d / c value is within a suitable range, through the interaction between calcium in the negative electrode film and the active material in the negative electrode sheet, the secondary battery maintains high capacity and high energy density while exhibiting low gas production rate, high kinetic performance, and cycle stability.

[0083] In some embodiments, based on the total mass of the negative electrode film, the mass percentage d of calcium in the negative electrode film is 2 ppm to 3000 ppm. In some embodiments, based on the total mass of the negative electrode film, the mass percentage d of calcium in the negative electrode film is 40 ppm to 2300 ppm.

[0084] In some embodiments, based on the total mass of the negative electrode film, the mass percentage d of calcium in the negative electrode film is 2ppm, 10ppm, 40ppm, 80ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1500ppm, 2000ppm, 2300ppm, 2500ppm, 3000ppm, or any value between these values.

[0085] In this article, ppm refers to parts per million.

[0086] When the mass percentage (d) of calcium in the negative electrode film is within a suitable range, it can reduce the negative impact of excessive calcium on the capacity and impedance of the secondary battery, while fully leveraging the role of calcium in suppressing dendrite formation and reducing gas production. This reduces battery gas production while improving the battery's low-temperature charging performance and room-temperature cycle capacity retention. When the mass percentage (d) of calcium in the negative electrode film is between 40 ppm and 2300 ppm, the battery gas production rate is further reduced, and the cycle stability is further improved.

[0087] In some embodiments, the actual discharge specific capacity of the negative electrode active material, measured by a three-stage step-discharge method (discharging at a rate of 0.05C within a voltage range of 0.1V-0.005V, followed by discharge at currents of 40μA and 10μA), is 100mAh / g-300mAh / g. In some embodiments, the actual discharge specific capacity of the negative electrode active material, measured by a three-stage step-discharge method (discharging at a rate of 0.05C within a voltage range of 0.1V-0.005V, followed by discharge at currents of 40μA and 10μA), is 200mAh / g-250mAh / g.

[0088] In some embodiments, the actual discharge specific capacity measured by the three-stage step-by-step discharge method, in which the negative electrode active material is first discharged at a rate of 0.05C in the voltage range of 0.1V-0.005V, and then discharged at currents of 40μA and 10μA, can be 100mAh / g, 150mAh / g, 200mAh / g, 250mAh / g, 300mAh / g, or any value between them.

[0089] The actual discharge specific capacity of the negative electrode active material in the voltage range of 0.1V-0.005V can be controlled by altering the preparation process of the negative electrode active material. Taking hard carbon as an example, by changing the pyrolysis temperature, the pore size and content of the negative electrode active material can be adjusted to achieve capacity control in different voltage ranges. Increasing the pyrolysis temperature helps induce the formation of ordered micropores in hard carbon, thereby improving the actual discharge specific capacity of the negative electrode active material in the 0.1V-0.005V voltage range.

[0090] When the actual discharge specific capacity of the negative electrode active material is within a suitable range in the 0.1V-0.005V voltage range, it can reduce the amount of gas generated after the battery is stored at high temperatures, and improve the battery's kinetic performance and cycle stability. When the actual discharge specific capacity of the negative electrode active material in the 0.1V-0.005V voltage range is 200mAh / g-250mAh / g, it can further balance the battery's high energy density and low gas generation.

[0091] In some embodiments, the negative electrode active material includes one or more of hard carbon, metallic sodium, sodium-tin alloy, and metal oxides.

[0092] In some embodiments, the negative electrode active material includes hard carbon.

[0093] In some embodiments, hard carbon is a negative electrode active material with a particle size of 1µm to 50µm prepared by calcining biomass materials once at 600℃-1000℃ for 1h-5h in an inert environment, grinding for 1h-4h, and then calcining them a second time at 1100℃-1800℃ for 2h-8h in an inert environment.

[0094] In some embodiments, the biomass material includes one or more of the following: peanut shells, straw, sawdust, walnut shells, bagasse, rice husks, wheat husks, coconut shells, apricot shells, wood, lignin, and papermaking waste.

[0095] In some embodiments, the temperature for a single calcination can be selected as 600°C, 700°C, 800°C, 900°C, 1000°C, or any value between the two.

[0096] In some implementations, the grinding time can be selected as 1h, 2h, 3h, 4h or any range between the two.

[0097] In some implementations, the calcination time can be selected as 1h, 2h, 3h, 4h, 5h or any value range between the two.

[0098] In some embodiments, the temperature for secondary calcination can be selected as 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, or any value range between the two.

[0099] In some implementations, the secondary calcination time can be selected as 2h, 3h, 4h, 5h, 6h, 7h, 8h, or any value range between the two.

[0100] In some embodiments, the particle size of the hard carbon is 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm or any value between two of these.

[0101] In some embodiments, the sodium secondary battery further includes a positive electrode sheet, which includes a positive electrode film layer containing a positive electrode active material.

[0102] In some embodiments, the positive electrode active material further contains copper, and the mass percentage of copper is 0.01% to 23% based on the total mass of the positive electrode active material, optionally 6.5% to 18%.

[0103] In some embodiments, based on the total mass of the positive electrode active material, the mass proportion of the copper element is 0.01%, 4%, 6.5%, 10%, 13%, 15%, 18%, 20%, 23%, or a numerical range between any two of them.

[0104] The positive electrode active material containing a copper element has a more stable structure, which can further improve the cycle stability of the battery.

[0105] When the mass proportion of the copper element is within a suitable range, while the cycle stability of the battery is improved, the copper element will not be converted into Cu at high voltage 3+ , which causes the electrolyte to accelerate decomposition under its high oxidizing property and sharply deteriorates the gas generation phenomenon of the battery. When the mass proportion of the copper element is in the range of 6.5% to 18%, the low gas production and high cycle stability of the secondary battery can be further balanced.

[0106] In some embodiments, the positive electrode active material may adopt a positive electrode active material well known in the art for batteries. As an example, the positive electrode active material may include at least one of the following materials: Prussian blue analogs, sodium-containing phosphates, sodium-containing transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials may be used alone, or two or more thereof may be used in combination. Wherein, the Prussian blue analog is Na x P[R(CN)6] δ ·zH2O, wherein P and R are each independently selected from at least one of transition metal elements, 0<x≤2, 0<δ≤1, and 0≤z≤10; the sodium-containing phosphate is Na b Me c (PO4) d , wherein Me is one or more of Ti, Cr, Mn, Fe, Co, Ni, V, Cu, and Zn, 0<b≤4, 0<c≤2, 1≤d≤3; the sodium-containing transition metal oxide is Na a M b N c Fe d Mn e O2, M and N include at least one of Sc, Ti, V, Cr, Co, Ni, Cu, Zn, Zr, Nb, Mo, Sn, Hf, Ta, W, and Pb, 0.05≤b≤0.2, 0.2≤c≤0.3, 0.2≤d≤0.3, 0.3≤e≤0.4, 0.75≤a / (b+c+d+e)≤1; In some embodiments, the positive electrode active material includes a sodium transition metal oxide, and the sodium transition metal oxide includes Na m Cu n Xo Fe p Mn q O 2-s, Where X includes one or more of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn, Fe, and Ba, 0 <m≤1,0≤n≤0.5,0≤o<0.5,0≤p≤0.5,0<q≤0 .68,n+o+p+q=1,0≤s<0.2。

[0107] Sodium transition metal oxide cathode active materials have high voltage. While the anionic oxygen contributes to capacity, it also generates a large amount of protonated hydrogen, accelerating the oxidation and gas production of unstable components in the negative electrode, resulting in severe gas production on the negative electrode side. Through the combined action of the negative electrode sheet provided in this application and the fluorocarbonate compounds in the electrolyte, battery gas production can be effectively reduced while improving battery capacity and energy density.

[0108] In some embodiments, the sodium transition metal oxide includes Na[Cu] 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2, Na 7 / 9 [Cu 2 / 9 Fe 1 / 9 Mn 2 / 3 O2, Na 9 / 10 [Cu 2 / 5 Fe 1 / 10 Mn 1 / 2 At least one of O2.

[0109] In some embodiments, the electrolyte further includes a second component, which is one or more of the following: vinylene carbonate, ethylene ethylene carbonate, 1,3-propane sulfonyl lactone, 1,3-propene sulfonate lactone, vinyl sulfate, maleic anhydride, succinic anhydride, sodium difluorooxalate borate, triallyl phosphate, sodium bis(oxalate borate), sodium tetrafluorooxalate phosphate, sodium difluorobis(oxalate) phosphate, sodium difluorophosphate, and sodium fluorosulfonate.

[0110] The SEI film formed at the negative electrode interface in sodium-ion batteries mainly consists of sodium alkyl carbonate and sodium carbonate. However, sodium alkyl carbonate has a higher solubility in the electrolyte solvent than lithium alkyl carbonate, making the SEI film of sodium-ion batteries highly unstable. This leads to continuous side reactions between the electrolyte and the negative electrode, resulting in poor cycle performance. A second component containing unsaturated functional groups can preferentially reduce to form a film at the negative electrode compared to the solvent. It works in conjunction with fluorocarbonate compounds to inhibit the formation of easily soluble substances such as sodium alkyl carbonate, and together with the negative electrode sheet, reduces gas production and improves battery cycle stability.

[0111] In some embodiments, the second component accounts for 0.01% to 10% of the total mass of the electrolyte. In some embodiments, the second component accounts for 0.1% to 5% of the total mass of the electrolyte.

[0112] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the second component can be selected as 0.01%, 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any value between them.

[0113] When the mass percentage of the second component is within the aforementioned range, it can improve the gas generation phenomenon in the battery while controlling the thickness of the SEI film, thereby simultaneously achieving low impedance and low gas generation in the battery.

[0114] In some embodiments, the electrolyte includes an electrolyte salt selected from at least one of NaPF6, NaBF4, NaN(SO2F)2 (NaFSI), NaClO4, NaAsF6, NaB(C2O4)2 (NaBOB), NaBF2(C2O4) (NaDFOB), NaN(SO2RF)2, and NaN(SO2F)(SO2RF), wherein RF represents C X1 F 2X1+1 X1 is an integer between 1 and 10, and can be an integer between 1 and 3.

[0115] In some embodiments, the electrolyte salt is selected from one or more of NaPF6, NaN(SO2F)2, NaN(CF3SO2)2, NaB(C2O4)2, and NaBF2(C2O4). In some embodiments, the electrolyte salt is selected from one or more of NaPF6, NaN(SO2RF)2, and NaBF2(C2O4). In some embodiments, RF is -CF3, -C2F5, or -CF2CF2CF3.

[0116] In some embodiments, the electrolyte includes a solvent, which includes at least one of the following: chain carbonates, chain carboxylic esters, cyclic carbonates, ether solvents, sulfone solvents, and nitrile solvents. In some embodiments, the chain carbonate includes at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), methyl propyl carbonate (MPC), methyl isopropyl carbonate (MIPC), methyl butyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and dibutyl carbonate. In some embodiments, the chain carbonate includes at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), and methyl propyl carbonate (MPC). In some embodiments, the chain carboxylic ester includes at least one of methyl formate (MF), ethyl formate (EF), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), ethyl butyrate (EB), methyl acetate (MA), ethyl acetate (EA), and propyl acetate (PA). In some embodiments, the chain carboxylic acid ester includes at least one selected from methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl acetate (MA), ethyl acetate (EA), and propyl acetate (PA). In some embodiments, the ether solvent includes at least one selected from dioxolane (DOL), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2Me-THF), tetrahydropyran (THP), 1,2-dimethoxyethane (DME), diethylene glycol dimethyl ether (DG), 1,2-diethoxyethane, and 1,2-dibutoxyethane.

[0117] [Positive electrode plate] A positive electrode typically includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, the positive electrode film layer including a positive electrode active material.

[0118] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0119] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0120] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0121] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0122] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0123] [Negative electrode plate] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0124] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0125] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil or aluminum foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0126] In some embodiments, the negative electrode film layer may optionally include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0127] In some embodiments, the negative electrode film may optionally include a conductive agent. As an example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0128] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0129] In some embodiments, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0130] [Isolation membrane] In some embodiments, the secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0131] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0132] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0133] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.

[0134] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0135] In this application, the shape of the sodium secondary battery includes, but is not limited to, cylindrical, square, or other arbitrary shapes. For example, Figure 2 This is an example of a square-structured sodium secondary battery.

[0136] In some implementations, refer to Figure 3The outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 can be placed over the opening to close the receiving cavity. The positive electrode, negative electrode, and separator may be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. ​​The sodium secondary battery 5 may contain one or more electrode assemblies 52, which can be selected by those skilled in the art according to specific practical needs.

[0137] In some embodiments, sodium secondary batteries can be assembled into battery modules, and the number of sodium secondary batteries contained in a battery module can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery module.

[0138] Figure 4 This is battery module 4, used as an example. (See reference...) Figure 4 In battery module 4, multiple sodium secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple sodium secondary batteries 5 can be fixed in place using fasteners.

[0139] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of sodium secondary batteries 5 are received.

[0140] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0141] Figure 5 and Figure 6 This is battery pack 1 as an example. (See reference...) Figure 5 and Figure 6 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0142] In addition, this application also provides an electrical device, which includes at least one of the sodium secondary battery, battery module, or battery pack provided in this application. The sodium secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0143] As an electrical device, sodium secondary batteries, battery modules, or battery packs can be selected according to their usage requirements.

[0144] Figure 7 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of sodium-ion batteries for this device, a battery pack or battery module can be used.

[0145] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use sodium-ion batteries as their power source.

[0146] Example The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0147] I. Preparation Method Example 1: 1) Electrolyte In an argon-atmospheric glove box (H2O content <10ppm, O2 content <1ppm), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of 30 / 70, and 1M NaPF6 sodium salt was dissolved. Then, fluoroethylene carbonate was added and stirred until homogeneous to prepare the electrolyte. Based on the total mass of the electrolyte, the mass percentage of fluoroethylene carbonate was 1%.

[0148] 2) Preparation of positive electrode active materials Na 7 / 9 Cu 2 / 9 Fe 1 / 9 Mn 2 / 3O2 preparation: 0.39 mol Na2CO3, 0.22 mol CuO, 0.06 mol Fe2O3 and 0.67 mol MnO2 precursor were ball-milled in a ball mill for 12 h with ethanol as the dispersant. After drying, the uniformly mixed powder was pressed into tablets at 20 MPa and sintered at 900 °C for 12 h to obtain the O2. The sintered powder needs to be quickly transferred to a glove box for storage.

[0149] 3) Preparation of the positive electrode C Na, the positive electrode active material 7 / 9 Cu 2 / 9 Fe 1 / 9 Mn 2 / 3 O2, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system at a weight ratio of 90:5:5 to obtain a positive electrode slurry; the positive electrode slurry was then mixed at a rate of 0.28 g (dry weight) / 1540.25 mm. 2 The density is uniformly coated on a 13μm thick positive electrode current collector aluminum foil; after the aluminum foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the positive electrode sheet.

[0150] 4) Preparation of negative electrode active materials The biomass material coconut shell was calcined at 800℃ for 2 hours in a tube furnace with an argon atmosphere. Then it was washed with hydrochloric acid and deionized water and dried. After grinding for 2 hours, it was calcined at 1550℃ for 4 hours in a tube furnace with an argon atmosphere to obtain the target material H2 with a particle size of 10μm. The actual discharge specific capacity was tested to be 40mAh / g in the 0.5V-1V voltage range and 220mAh / g in the 0.1V-0.005V voltage range. For the specific test method, please refer to the "Actual Discharge Specific Capacity Test of Negative Electrode Active Material" section below.

[0151] 5) Preparation of negative electrode plate C The negative electrode active material H2, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) were thoroughly mixed in a deionized water solvent system at a weight ratio of 90:4:4:2. A certain amount of CaO was added to make the calcium content in the dry slurry (i.e., the total mass of negative electrode active material H2, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC-Na), and CaO) 100 ppm, thus obtaining the negative electrode slurry. The negative electrode slurry was then measured at 0.14 g (dry weight) / 1540.25 mm. 2 The amount of coating is uniformly coated on a 13μm thick negative electrode current collector copper foil; after the copper foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the negative electrode sheet.

[0152] 6) Separating membrane A 9μm porous polyethylene (PE) polymer film was used as the separator.

[0153] 7) Battery manufacturing The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to isolate them. The cells are then wound to obtain a bare cell. The tabs are welded on, and the bare cell is placed in an outer package. The electrolyte prepared above is injected into the dried cell. After processes such as encapsulation, settling, formation, shaping, and capacity testing, the sodium secondary battery product of Example 1 is obtained.

[0154] The preparation methods of sodium secondary batteries in Examples 2-4 are basically the same as those in Example 1, except that the types of fluorocarbonate compounds are adjusted. Specific parameters are shown in Table 1.

[0155] The preparation methods of sodium secondary batteries in Examples 5-8 are basically the same as those in Example 1, except that the mass ratio of fluorinated carbonate compounds is adjusted. Specific parameters are shown in Table 1.

[0156] The preparation methods of sodium secondary batteries in Examples 9-12 are basically the same as those in Example 1, except that the preparation processes of the negative electrode active material and the negative electrode sheet are adjusted to adjust the actual discharge specific capacity of the negative electrode active material in the negative electrode sheet in the voltage range of 1.0V-0.5V and the actual discharge specific capacity in the voltage range of 0.1V-0.005V. Specific parameters are shown in Table 1, and the preparation process is as follows: In Example 9, the actual discharge specific capacity of the negative electrode active material in negative electrode A, measured by a three-stage step-discharge method (discharging at a rate of 0.05C first, then discharging at currents of 40μA and 10μA) in the voltage range of 1.0V-0.5V, was 9 mAh / g; the actual discharge specific capacity measured by the same three-stage step-discharge method (discharging at a rate of 0.05C first, then discharging at currents of 40μA and 10μA) in the voltage range of 0.1V-0.005V, was 300 mAh / g. Detailed testing methods are described in the testing methods section below. The negative electrode preparation method is as follows: The biomass material coconut shell was calcined at 800℃ for 2 hours in a tube furnace with an argon atmosphere. Then it was washed with hydrochloric acid and deionized water and dried. After grinding for 2 hours, it was calcined at 1650℃ for 6 hours in a tube furnace with an argon atmosphere to obtain the target material H3 with a particle size of 20μm.

[0157] The negative electrode active material H3, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) were thoroughly mixed in a deionized water solvent system at a weight ratio of 90:4:4:2. A certain amount of CaO was added to make the calcium content in the dry material 100ppm, thus obtaining the negative electrode slurry. The negative electrode slurry was then mixed at a ratio of 0.14g (dry weight) / 1540.25mm. 2 The amount of coating is uniformly coated on a 13μm thick negative electrode current collector copper foil; after the copper foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the negative electrode sheet.

[0158] In Example 10, the actual discharge specific capacity of the negative electrode active material in negative electrode plate B is 18.3 mAh / g in the voltage range of 1.0V-0.5V and 250 mAh / g in the voltage range of 0.1V-0.005V. Detailed testing methods are described in the testing methods section below. The preparation method is as follows: The negative electrode active material (30wt% H2 and 70wt% H3), conductive agent acetylene black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) were thoroughly mixed in a deionized water solvent system at a weight ratio of 90:4:4:2. A certain amount of CaO was added to make the calcium content in the dry material 100ppm, thus obtaining the negative electrode slurry. The negative electrode slurry was then mixed at a rate of 0.14g (dry weight) / 1540.25mm. 2 The amount of coating is uniformly coated on a 13μm thick negative electrode current collector copper foil; after the copper foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the negative electrode sheet.

[0159] In Example 11, the actual discharge specific capacity of the negative electrode active material in negative electrode E, measured by a three-stage step-discharge method (discharging at a rate of 0.05C first, then discharging at currents of 40μA and 10μA in the voltage range of 1.0V-0.5V), was 140mAh / g; the actual discharge capacity measured by the same three-stage step-discharge method (discharging at a rate of 0.05C first, then discharging at currents of 40μA and 10μA in the voltage range of 0.1V-0.005V) was 100mAh / g. Detailed testing methods are described in the testing methods section below. The negative electrode preparation method is as follows: The biomass material coconut shell was calcined at 800℃ for 2 hours in a tube furnace with an argon atmosphere. Then it was washed and dried with hydrochloric acid and deionized water, respectively. After grinding for 2 hours, it was calcined at 1150℃ for 2 hours in a tube furnace with an argon atmosphere to obtain the target material H1 with a particle size of 2μm.

[0160] The negative electrode active material H1, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) were thoroughly mixed in a deionized water solvent system at a weight ratio of 90:4:4:2. A certain amount of CaO was added to make the calcium content in the dry material 100ppm, thus obtaining the negative electrode slurry. The negative electrode slurry was then mixed at a ratio of 0.14g (dry weight) / 1540.25mm. 2 The amount of coating is uniformly coated on a 13μm thick negative electrode current collector copper foil; after the copper foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the negative electrode sheet.

[0161] In Example 12, the actual discharge specific capacity of the negative electrode active material in negative electrode plate D, measured by a three-stage step-discharge method (discharging at a rate of 0.05C first, then discharging at currents of 40μA and 10μA) in the voltage range of 1.0V-0.5V, was 70mAh / g; the actual discharge specific capacity measured by the same three-stage step-discharge method (discharging at a rate of 0.05C first, then discharging at currents of 40μA and 10μA) in the voltage range of 0.1V-0V, was 200mAh / g. Detailed testing methods are described in the testing methods section below. The preparation method is as follows: The negative electrode active material (30wt% H1 and 70wt% H2), conductive agent acetylene black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were thoroughly mixed in a deionized water solvent system at a weight ratio of 90:4:4:2. A certain amount of CaO was added to make the calcium content in the dry material 100ppm, thus obtaining the negative electrode slurry. The negative electrode slurry was then mixed at a rate of 0.14g (dry weight) / 1540.25mm. 2 The amount of coating is uniformly applied to a negative electrode current collector copper foil with a thickness of 8μm; after the copper foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the negative electrode sheet.

[0162] The preparation methods of sodium secondary batteries in Examples 13-18 are basically the same as those in Example 1. The difference is that the mass ratio of calcium in the negative electrode film is adjusted by adding different amounts of CaO to the negative electrode slurry. The specific parameters are shown in Table 1.

[0163] The preparation methods of sodium secondary batteries in Examples 19-22 are basically the same as those in Example 1, except that the preparation processes of the positive electrode active material and the positive electrode sheet are adjusted to adjust the mass ratio of copper in the positive electrode active material. Specific parameters are shown in Table 1, and the preparation process is as follows: In Example 19, the copper content of the positive electrode active material in positive electrode plate A is 0%, and the preparation method is as follows: Na 1 / 2 Fe 1 / 2 Mn 1 / 2Preparation of O2: 0.25 mol Na2CO3, 0.25 mol Fe2O3 and 0.5 mol MnO2 precursors were ball-milled in a ball mill for 12 h with ethanol as the dispersant. After drying, the uniformly mixed powder was pressed into tablets at 20 MPa and sintered at 900 °C for 12 h to obtain O2. The sintered powder needs to be quickly transferred to a glove box for storage.

[0164] Na, the positive electrode active material 1 / 2 Fe 1 / 2 Mn 1 / 2 O2, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system at a weight ratio of 90:5:5 to obtain a positive electrode slurry; the positive electrode slurry was then mixed at a rate of 0.28 g (dry weight) / 1540.25 mm. 2 The amount of material is evenly coated onto a 13μm thick positive current collector aluminum foil; after the aluminum foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the positive electrode sheet.

[0165] In Example 20, the copper element in the positive electrode active material of positive electrode plate B accounts for 6.5% by mass, and the preparation method is as follows: The positive electrode active material (50wt% Na) 1 / 2 Fe 1 / 2 Mn 1 / 2 O2 and 50wt% Na 7 / 9 Cu 2 / 9 Fe 1 / 9 Mn 2 / 3 O2), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system at a weight ratio of 90:5:5 to obtain a positive electrode slurry; the positive electrode slurry was then mixed at a rate of 0.28 g (dry weight) / 1540.25 mm. 2 The amount of material is evenly coated onto a 13μm thick positive current collector aluminum foil; after the aluminum foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the positive electrode sheet.

[0166] In Example 21, the copper element in the positive electrode active material of the positive electrode plate E accounts for 23% by mass, and the preparation method is as follows: Na 9 / 10 Cu 2 / 5 Fe 1 / 10 Mn 1 / 2O2 preparation: 0.45 mol Na2CO3, 0.4 mol CuO, 0.05 mol Fe2O3 and 0.5 mol MnO2 precursor were ball-milled in a ball mill for 12 h with ethanol as the dispersant. After drying, the uniformly mixed powder was pressed into tablets at 20 MPa and sintered at 900 °C for 12 h to obtain the O2. The sintered powder needs to be quickly transferred to a glove box for storage.

[0167] Na, the positive electrode active material 9 / 10 Cu 2 / 5 Fe 1 / 10 Mn 1 / 2 O2, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system at a weight ratio of 90:5:5 to obtain a positive electrode slurry; the positive electrode slurry was then mixed at a rate of 0.28 g (dry weight) / 1540.25 mm. 2 The amount of material is evenly coated onto a 13μm thick positive current collector aluminum foil; after the aluminum foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the positive electrode sheet.

[0168] In Example 22, the copper element in the positive electrode active material of the positive electrode plate D accounts for 18% by mass. The preparation method is as follows: The positive electrode active material (50wt% Na) 7 / 9 Cu 2 / 9 Fe 1 / 9 Mn 2 / 3 O2 and 50wt% Na 9 / 10 Cu 2 / 5 Fe 1 / 10 Mn 1 / 2 O2), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system at a weight ratio of 90:5:5 to obtain a positive electrode slurry; the positive electrode slurry was then mixed at a rate of 0.28 g (dry weight) / 1540.25 mm. 2 The amount of material is evenly coated onto a 13μm thick positive current collector aluminum foil; after the aluminum foil is dried at room temperature, it is transferred to a 120℃ oven to dry for 1 hour, and then cold-pressed and slit to obtain the positive electrode sheet.

[0169] The preparation methods of sodium secondary batteries in Examples 23-25 ​​are basically the same as those in Example 1, except that a second component is added. The specific parameters are shown in Table 1.

[0170] The preparation method of the sodium secondary battery in Comparative Example 1 is basically the same as that in Example 9, except that the mass percentage of fluoroethylene carbonate in the electrolyte in Comparative Example 1 is 0.01%. The preparation method of the sodium secondary battery in Comparative Example 2 is basically the same as that in Example 1, except that the electrolyte does not contain fluorinated carbonate compounds.

[0171] II. Battery Performance Testing 1. High-temperature storage volume change rate At 25°C, the novel sodium secondary batteries prepared in the examples and comparative examples were left to stand for 5 minutes, then charged at a constant current of 1C to 4.0V, and then charged at a constant voltage until the current was less than or equal to 0.05C. After that, they were left to stand for 5 minutes, and then discharged at a constant current of 1C to 1.5V. The volume V1 of the battery was tested by the water displacement method. Then the battery was placed in a 60°C oven and stored for 2 months. After that, the battery was taken out and the volume was tested as V2. The volume change rate of the battery was = (V2-V1) / V1×100%.

[0172] 2. Low-temperature charging performance at -10℃ A three-electrode battery with a reference electrode, sodium vanadium phosphate, was prepared. The battery was charged at 25°C with a constant current of 1C to a voltage of 4.0V, then charged at a constant voltage until the current was less than or equal to 0.05C. After resting for 5 minutes, it was discharged at a constant current of 1C to 1.5V, and the discharge capacity was recorded as C1. The battery was then placed in a -10°C environment and left to stand for 2 hours, followed by constant current charging at 0.1C to a voltage of 4.0V. The charging capacity at the negative electrode potential before the reference potential reached -3.377V was obtained as C2. The charging capability of the battery at -10°C was calculated as C2 / C1 × 100%.

[0173] 3. Mass energy density Battery cell capacity testing: The battery cell was left to stand at 25°C for 2 hours to ensure the temperature remained at 25°C. At 25°C, the battery cell was charged at 0.1C to the charging cutoff voltage, and then continued to be charged at this cutoff voltage under constant voltage until the current reached 0.05C, at which point charging was stopped (where C represents the rated capacity of the battery cell). The battery cell was then left to stand at 25°C for 1 hour. At 25°C, the battery cell was discharged at 0.1C to the discharge cutoff voltage, and the total discharge capacity C0 and total discharge energy E0 of the battery cell were recorded.

[0174] Battery cell weight measurement: Place the battery cell on an electronic balance until the weight stabilizes, and read the battery cell weight value M0.

[0175] Energy density calculation: The energy density of a battery cell is calculated as the discharge energy E0 of the battery cell divided by the weight M0 of the battery cell.

[0176] 4. Battery cycle capacity retention rate At 25°C, the prepared battery was charged to 4.0V with a constant current of 1C, and then charged to 0.05C with a constant voltage of 4.0V. After standing for 5 minutes, it was discharged to 1.5V with a constant current of 1C. This is the first charge / discharge cycle of the battery, and the discharge capacity of this cycle is recorded as the discharge capacity of the battery in the first cycle (C0). The above steps were repeated for the same battery. The discharge capacity of the battery after 400 cycles (C1) was recorded. The capacity retention rate after 400 cycles is calculated as C1 / C0 × 100%.

[0177] 5. Actual discharge specific capacity test of negative electrode active material The negative electrode sheets from the comparative and examples were punched into small circular pieces with a diameter of 14 mm to serve as the positive electrode in the coin cell. A sodium metal sheet was used as the negative electrode, and a polypropylene membrane as the separator. A 1.3 mol / L sodium hexafluorophosphate solution was used as the electrolyte, containing ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a mass ratio of 1:2:2. This electrolyte was used to assemble coin cells, and constant current charge-discharge tests were conducted in the 0.005-2V voltage range. During discharge, the cells were discharged at a constant current rate of 0.05C to 0.005V, allowed to stand until the voltage stabilized, and then discharged at a constant current rate of 40 μA to 0.005V. After standing until the voltage stabilized, the cells were discharged at a constant current rate of 40 μA to 0.005V. The material is discharged at a constant current rate of 10μA to 0.005V, and then charged at a constant current rate of 0.05C to 2V. The total discharge capacity (mAh) of the second discharge cycle in the voltage range of 1.0V-0.5V is divided by the mass (g) of the negative electrode active material in the negative electrode sheet. This is recorded as the actual discharge specific capacity (mAh / g) of the negative electrode active material in the voltage range of 1.0V-0.5V. Similarly, the total discharge capacity (mAh) of the second discharge cycle in the voltage range of 0.1V-0.005V is divided by the mass (g) of the negative electrode active material in the negative electrode sheet. This is recorded as the actual discharge specific capacity (mAh / g) of the negative electrode active material in the voltage range of 0.1V-0.005V.

[0178] The theoretical discharge specific capacity of the negative electrode active material, hard carbon, is 300 mAh / g.

[0179] 6. Determination of the mass percentage of calcium in the negative electrode film layer The mass percentage of calcium in the negative electrode film can be determined according to the general rule EPA 6010D-2014, using inductively coupled plasma atomic emission spectrometry. The mass percentage of silicon in the negative electrode film is calculated by dividing the mass of calcium in the negative electrode film sample by the mass of the negative electrode film sample.

[0180] 7. Determination of the mass percentage of copper in the positive electrode active material The mass percentage of Cu in the positive electrode active material can be determined according to the general rule EPA 6010D-2014, using inductively coupled plasma atomic emission spectrometry. The mass percentage of Cu in the positive electrode active material is calculated by dividing the mass of Cu in the positive electrode active material sample by the mass of the positive electrode active material sample.

[0181] III. Analysis of Test Results for Each Embodiment and Comparative Example Batteries for each embodiment and comparative example were prepared according to the above method, and various performance parameters were measured. The results are shown in the table below.

[0182] Table 1

[0183] Table 2

[0184] Table 3

[0185] Table 4

[0186] Based on the above results, it can be seen that the sodium secondary batteries in Examples 1-25 all include a negative electrode sheet and an electrolyte. The negative electrode sheet includes a negative electrode active material, and the ratio of the actual discharge specific capacity of the negative electrode active material in the voltage range of 1.0V-0.5V to the theoretical discharge specific capacity of the negative electrode active material is a. The electrolyte includes a first component, which is a fluorocarbonate compound. Based on the total mass of the electrolyte, the mass percentage of the fluorocarbonate compound is b. And a and b satisfy: 1≤a / b≤270.

[0187] As can be seen from the comparison of the examples and comparative examples, when a and b satisfy the condition 1≤a / b≤270, the battery has a low battery volume expansion rate after high temperature storage, excellent low temperature charging performance, and room temperature cycle capacity retention.

[0188] As can be seen from the examples, when a and b satisfy 1≤a / b≤100, the volume expansion rate, low-temperature charging performance and room-temperature cycle capacity retention of the battery are further improved.

[0189] As can be seen from Examples 1 and 5-8, based on the total mass of the electrolyte, when the mass percentage (b) of fluoroethylene carbonate in the electrolyte is 0.05%-10%, the battery exhibits low volume expansion rate after high-temperature storage, excellent low-temperature charging performance, and good capacity retention during room-temperature cycling. When the mass percentage (b) of fluoroethylene carbonate in the electrolyte is 0.2%-10%, the volume expansion rate after high-temperature storage can be further reduced, and the low-temperature charging performance and capacity retention during room-temperature cycling can be improved.

[0190] As can be seen from Examples 1 and 9-12, when the actual discharge specific capacity of the negative electrode active material is 9 mAh / g-140 mAh / g in the 1.0V-0.5V voltage range and 100 mAh / g-300 mAh / g in the 0.1V-0.005V voltage range, the battery exhibits low volume expansion rate after high-temperature storage, excellent low-temperature charging performance, and room-temperature cycle capacity retention. When the discharge specific capacity of the negative electrode active material is 18 mAh / g-70 mAh / g in the 1.0V-0.5V voltage range and 200 mAh / g-250 mAh / g in the 1.0V-0.005V voltage range, the battery can balance low volume expansion rate after high-temperature storage, excellent low-temperature charging performance, room-temperature cycle capacity retention, and high energy density.

[0191] As can be seen from Examples 1 and 9-18, based on the total mass of the negative electrode film, the mass ratio of calcium in the negative electrode film is d, and the ratio of the actual discharge specific capacity of the negative electrode active material in the 0.1V-0.005V voltage range to the theoretical discharge specific capacity of the negative electrode active material is c. When d and c satisfy the following conditions: d / c = 2.5 × 10⁻⁶ ≤ d / c ≤ 4.5 × 10⁻³, the battery exhibits low volume expansion rate after high-temperature storage, excellent low-temperature charging performance, and room-temperature cycle capacity retention. When d and c satisfy 5.5 × 10⁻⁵ ≤ d / c ≤ 3.1 × 10⁻³, the battery balances low volume expansion rate after high-temperature storage with excellent low-temperature charging performance and room-temperature cycle capacity retention.

[0192] As can be seen from Examples 1 and 13-18, based on the total mass of the negative electrode film, when the mass percentage d of calcium in the negative electrode film is 40ppm to 3000ppm, the battery volume expansion rate after high-temperature storage can be further reduced, and the low-temperature charging performance and room-temperature cycle capacity retention rate can be further improved.

[0193] As can be seen from Examples 1 and 19-22, based on the total mass of the positive electrode active material, when the mass percentage of copper is 0% to 23%, the battery exhibits low volume expansion rate after high-temperature storage, excellent low-temperature charging performance, and room-temperature cycle capacity retention. When the mass percentage of copper is 6.5% to 18%, the battery balances low volume expansion rate after high-temperature storage with excellent low-temperature charging performance and room-temperature cycle capacity retention.

[0194] As can be seen from Examples 1 and 23-25, the addition of a second component to the electrolyte results in a lower battery volume expansion rate after high-temperature storage, superior low-temperature charging performance, and better capacity retention during room-temperature cycling.

[0195] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A sodium secondary battery, wherein, include: A negative electrode sheet, wherein the negative electrode sheet includes a negative electrode film layer, the negative electrode film layer contains calcium element, and based on the total mass of the negative electrode film layer, the mass percentage d of the calcium element in the negative electrode film layer is 2ppm~3000ppm; The negative electrode film layer includes a negative electrode active material, which includes hard carbon; and The electrolyte comprises a second component, which includes one or more of the following: vinylene carbonate, ethylene ethylene carbonate, 1,3-propane sulfonyl lactone, 1,3-propene sulfonate lactone, vinyl sulfate, maleic anhydride, succinic anhydride, sodium difluorooxalate borate, triallyl phosphate, sodium bis(oxalate borate), sodium tetrafluorooxalate phosphate, sodium difluorobis(oxalate) phosphate, sodium difluorophosphate, and sodium fluorosulfonate.

2. The sodium secondary battery according to claim 1, wherein, The ratio of the actual discharge specific capacity of the negative electrode active material measured by a three-stage stepwise discharge method (discharging at a rate of 0.05C in the voltage range of 1.0V-0.5V, and then discharging at currents of 40μA and 10μA) to the theoretical discharge specific capacity of the negative electrode active material is a, where a is 0.03~0.

47.

3. The sodium secondary battery according to claim 2, wherein, The electrolyte also includes a first component, which is a fluorocarbonate compound. Based on the total mass of the electrolyte, the mass percentage of the fluorocarbonate compound is b, where b is 0.05% to 10%.

4. The sodium secondary battery according to claim 3, wherein, a and b satisfy: 1 ​​≤ a / b ≤ 270.

5. The sodium secondary battery according to claim 3, wherein, a and b satisfy: 1 ​​≤ a / b ≤ 100.

6. The sodium secondary battery according to claim 3, wherein, a and b satisfy: 1≤a / b≤67.

7. The sodium secondary battery according to claim 2, wherein, The actual discharge specific capacity of the negative electrode active material, measured by a three-stage step-by-step discharge method (discharging at a rate of 0.05C first, and then discharging at currents of 40μA and 10μA within a voltage range of 1.0V-0.5V), is 9mAh / g-140mAh / g.

8. The sodium secondary battery according to claim 2, wherein, The actual discharge specific capacity of the negative electrode active material, measured by a three-stage step-by-step discharge method (discharging at a rate of 0.05C first, and then discharging at currents of 40μA and 10μA in the voltage range of 1.0V-0.5V), is 18mAh / g-70mAh / g.

9. The sodium secondary battery according to claim 1, wherein, The particle size of the negative electrode active material is 1μm~50μm.

10. The sodium secondary battery according to claim 1, wherein, The particle size of the negative electrode active material is 2μm~20μm.

11. The sodium secondary battery according to claim 3, wherein, Based on the total mass of the electrolyte, the mass percentage b of the fluorocarbonate compound is 0.2% to 10%.

12. The sodium secondary battery according to claim 3, wherein, The fluorocarbonate compounds include those shown in Formula I. Formula I Among them, R1, R2, R3, and R4 each independently include hydrogen atoms, halogen atoms, and carbon atoms. 1-6 hydrocarbon group, C 1-3 Haloalkyl, C 1-3 Alkoxy, C 1-3 At least one of haloalkoxy, ester, cyano, sulfonic acid, and isocyanate groups; and at least one of R1, R2, R3, and R4 is a fluorine atom.

13. The sodium secondary battery according to claim 12, wherein, The fluorocarbonate compound includes at least one of the following compounds. Formula II-1 Formula II-2 Formula II-3 Formula II-4 Formula II-5 Formula II-6 Formula II-7 Formula II-8 Formula II-9 Formula II-10.

14. The sodium secondary battery according to claim 1, wherein, Based on the total mass of the negative electrode film, the ratio of the actual discharge specific capacity measured by the three-stage step-by-step discharge method (discharging at a rate of 0.05C first, then at currents of 40μA and 10μA) to the theoretical discharge specific capacity of the negative electrode active material in the voltage range of 0.1V-0.005V is c, and d and c satisfy: 2.5×10 -6 ≤d / c≤4.5×10 -3 .

15. The sodium secondary battery according to claim 14, wherein, d and c satisfy: 2.7 × 10 -6 ≤d / c≤4.1×10 -3 .

16. The sodium secondary battery according to claim 14, wherein, d and c satisfy: 5.5 × 10 -5 ≤d / c≤3.1×10 -3 .

17. The sodium secondary battery according to claim 1, wherein, Based on the total mass of the negative electrode film, the mass percentage d of calcium in the negative electrode film is 40ppm to 2300ppm.

18. The sodium secondary battery according to any one of claims 1 to 17, wherein, The actual discharge specific capacity of the negative electrode active material, measured by a three-stage step-by-step discharge method (discharging at a rate of 0.05C in the voltage range of 0.1V-0.005V, followed by discharge at currents of 40μA and 10μA), is 100mAh / g-300mAh / g.

19. The sodium secondary battery according to any one of claims 1 to 17, wherein, The actual discharge specific capacity of the negative electrode active material, measured by a three-stage step-by-step discharge method (discharging at a rate of 0.05C in the voltage range of 0.1V-0.005V, followed by discharge at currents of 40μA and 10μA), is 200mAh / g-250mAh / g.

20. The sodium secondary battery according to claim 1, wherein, The sodium secondary battery also includes a positive electrode sheet, which comprises a positive electrode active material.

21. The sodium secondary battery according to claim 20, wherein, The positive electrode active material also contains copper, and the mass percentage of copper is 0.01% to 23% based on the total mass of the positive electrode active material.

22. The sodium secondary battery according to claim 21, wherein, Based on the total mass of the positive electrode active material, the mass percentage of copper is 6.5% to 18%.

23. The sodium secondary battery according to any one of claims 20-22, wherein, The positive electrode active material includes a sodium transition metal oxide, which includes Na. m Cu n X o Fe p Mn q O 2-s, Where X includes one or more of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn, Fe, and Ba, 0 <m≤1,0≤n≤0.5,0≤o<0.5,0≤p≤0.5,0<q≤0 .68,n+o+p+q=1,0≤s<0.2。 24. The sodium secondary battery according to claim 23, wherein, The sodium transition metal oxide includes Na[Cu] 1 / 9Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O2, Na 7 / 9 [Cu 2 / 9 Fe 1 / 9 Mn 2 / 3 O2, Na 9 / 10 [Cu 2 / 5 Fe 1 / 10 Mn 1 / 2 At least one of O2.

25. The sodium secondary battery according to claim 1, wherein, The second component includes one or more of 1,3-propanesulfonyl lactone, 1,3-propenesulfonyl lactone, sodium difluorooxalate borate, sodium difluorophosphate, and sodium fluorosulfonate.

26. The sodium secondary battery according to claim 1, wherein, Based on the total mass of the electrolyte, the mass percentage of the second component is 0.01% to 10%.

27. The sodium secondary battery according to claim 1, wherein, Based on the total mass of the electrolyte, the mass percentage of the second component is 0.1% to 5%.

28. The sodium secondary battery according to claim 1, wherein, Based on the total mass of the electrolyte, the mass percentage of the second component is 0.5% to 5%.

29. The sodium secondary battery according to claim 1, wherein, The electrolyte includes a solvent, which includes one or more of the following: chain carbonates, chain carboxylic esters, cyclic carbonates, ether solvents, sulfone solvents, and nitrile solvents.

30. The sodium secondary battery according to claim 1, wherein, The electrolyte comprises an electrolyte salt, which includes one or more of NaPF6, NaBF4, NaN(SO2F)2 (NaFSI), NaClO4, NaAsF6, NaB(C2O4)2 (NaBOB), NaBF2(C2O4) (NaDFOB), NaN(SO2RF)2, and NaN(SO2F)(SO2RF), wherein RF represents C X1 F 2X1+1 X1 is an integer between 1 and 10, and can be an integer between 1 and 3.

31. An electrical device, wherein, The sodium secondary battery includes any one of claims 1 to 30.

Citation Information

Patent Citations

  • Anti-malaria drug

    EP0001796A1

  • Expanded polyolefine sheet, process for its manufacture and wall covering of expanded polyolefine

    EP0001807A1